Tìm x 4x^2 – 9 – x ( 2x – 3 ) = 0

Tìm x

4x^2 – 9 – x ( 2x – 3 ) = 0

2 bình luận về “Tìm x 4x^2 – 9 – x ( 2x – 3 ) = 0”

  1. Lời giải:
    4x^2-9-x(2x-3)=0
    =>(2x-3)(2x+3)-x(2x-3)=0
    =>(2x-3)(2x+3-x)=0
    =>(2x-3)(x+3)=0
    =>(2x-3)(x+3)=0
    =>[(2x-3=0),(x+3=0):}
    =>[(x=3/2),(x=-3):}
    Vậy x\in{3/2;-3}

    Trả lời
  2. Giải đáp+Lời giải và giải thích chi tiết:
    4x^2 -9-x(2x-3)=0
    <=>(2x)^2 -3^2 -x(2x-3)=0
    <=>(2x-3)(2x+3)-x(2x-3)=0
    <=>(2x-3)(2x+3-x)=0
    <=>(2x-3)(x+3)=0
    <=> [2x3=0x+3=0 
    <=> [x=32x=3 
    Vậy x\in{3/2;-3}

    Trả lời

Viết một bình luận

Câu hỏi mới